Distribution and estimation of economic losses due to long-tailed macaque in the sago agroindustry in Lingga District, Riau Islands, Indonesia - ANGELITA SYAWALINA PRAMESWARI; BURHANUDDIN MASY’UD; ERVIZAL A. M. ZUHUD; PRIMADHIKA AL MANAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Prameswari AS, Masy’ud B, Zuhud EAM, Al Manar P. 2025. Distribution and estimation of economic losses due to long-tailed macaque in the sago agroindustry in Lingga District, Riau Islands, Indonesia. Biodiversitas 26: 5385-5394. The long-tailed macaque (Macaca fascicularis) is an opportunistic primate that frequently interacts with community-based agricultural systems, including the sago agroindustry in Lingga District, Riau Islands, Indonesia. Such interactions can cause material losses and threaten the sustainability of local livelihoods. This study aimed to analyze the population distribution, age structure, and economic impact of sago log damage caused by macaques. Field surveys were conducted using line transects, spatial analysis using ArcGIS 10.8, and structured interviews with sago farmers. The results recorded 18 groups comprising 116 individuals, with an average population density of 10.74 individuals/km². Sub-adults represented the dominant age class, displaying the highest levels of foraging and social activity, which increased their contact with stored sago logs. The average log damage reached 11,860.63±1,519.95 cm³ (9.56±1.22%), corresponding to a starch loss of 1.61±0.26 kg per log and annual economic losses of approximately IDR 22.7±3.6 million. Although local communities employ traditional deterrents, such as covering sago logs with sea sand and sago fronds, their effectiveness remains limited owing to inconsistent application and high labor requirements. This study provides one of the first empirical estimates of wildlife-induced post-harvest losses in the sago sector and highlights the need for integrated mitigation strategies that combine traditional ecological knowledge with scientific approaches, including physical barriers, habitat management, and buffer crop planting. Such integrative, community-based management is essential to minimize economic losses, mitigate human-wildlife conflict, and enhance the long-term sustainability of the sago-based agroindustry.